Guidance of The Literacy Culture Improvement Movement in State Elementary School 091700 Hubuan - Anggun Tiur Ida Sinaga; Benjamin Albert Simamora; Elvrida Yolanda Sinaga; Enjelina Simbolon (PT. TAROMBO RESEARCH DEVELOPMENT, 2026)
This community service activity aims to foster a literacy culture for SDN 091700 Hubuan students through assistance in making reading corners, getting used to reading 15 minutes before learning takes place, creating a text-rich environment so that students get used to reading. The stages of implementing this community service activity are as follows: (1) Field observation stage, (2) Activities socialization stage, (3) Mentoring stage. The results and reports of these community service activities will be published in local journals. This community service activity in the form of assistance in making a reading corner aims to provide knowledge in increasing interest and literacy culture at SDN 091700 Hubuan school in Simalungun Regency, North Sumatra, where based on observations the reading interest of students at SD Negeri 091700 is still very low . For this reason, socialization is needed to increase students' interest in reading. Increasing literacy culture can be started from schools through books in the library. To support a literacy culture, schools must have adequate facilities and infrastructure, especially the procurement of books in the library. The problems at SDN Negeri 091700 Hubuan include the absence of a library and a lack of books so that students rarely read at school. Students only read the textbook lessons when learning takes place. So that literacy activities become taboo